2011
DOI: 10.1093/bja/aer084
|View full text |Cite
|
Sign up to set email alerts
|

Oral oxycodone offers equivalent analgesia to intravenous patient-controlled analgesia after total hip replacement: a randomized, single-centre, non-blinded, non-inferiority study

Abstract: Oral analgesia with OOXY after THR offers non-inferior analgesia to IVPCA and may offer some logistical and cost advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 21 publications
(19 reference statements)
2
29
0
Order By: Relevance
“…20,21 At the same time, it has been shown that regularly scheduled sustained-release oxycodone administration, versus as-needed opioid analgesics, increases the rate of postoperative †OSA was determined by a history of previous diagnosis (n = 516) or positive screen for OSA during immediate preoperative assessment (n = 375). 6 ‡One patient was administered 75 mg pregabalin, which was categorized in the low-dose gabapentin category.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 At the same time, it has been shown that regularly scheduled sustained-release oxycodone administration, versus as-needed opioid analgesics, increases the rate of postoperative †OSA was determined by a history of previous diagnosis (n = 516) or positive screen for OSA during immediate preoperative assessment (n = 375). 6 ‡One patient was administered 75 mg pregabalin, which was categorized in the low-dose gabapentin category.…”
Section: Discussionmentioning
confidence: 99%
“…After orthopaedic surgery with postoperative opioid pain therapy, constipation was associated with a hospital stay prolonged by 1.4 days [6]. In another study, opioid-related ADEs including constipation after orthopedic surgery were associated with both hospital stay prolonged by 0.5 days and increased hospital costs [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Controlled-release oxycodone formulations provide relatively constant plasma concentrations [11] and seem to be feasible options in the treatment of postoperative pain [12, 13]. Oxycodone-naloxone controlled-release tablets are increasingly used for postoperative pain in order to decrease the risk of OIC [14], and preliminary experience suggests that this combination may also decrease other opioid-induced adverse events, like urinary retention [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some recent clinical trials and reviews/ meta-analyses show that oxycodone is similar in effectiveness to morphine, [61][62][63][64] and hydromorphone. [65] A recent meta-analysis of oxycodone versus other strong opioids (n=37 studies and 7 randomized clinical trials, 613 cancer patients with moderate to severe pain) found in 4 studies that oxycodone was significantly better than other strong opioids in reducing pain intensity in cancer patients and in seven studies there was a significant difference favoring oxycodone for effective pain relieve in cancer pain.…”
Section: Selecting the Right Opioid: When Can Ir Oxycodone Be A Good mentioning
confidence: 99%